Against the odds: exploring individuals’ pushback mechanisms against commercialized football gambling - Adebisi, Tunde; Aregbesola, Ayooluwa; Taiwo-Abdul, Timilehin (Frontiers in Public Health, 2024)
The need for money, the pursuit of pleasure, and the liberalised access to gambling have been documented in several pieces of literature as the drivers of gambling. Such drivers are predicated on commercialised gambling, leading to the growth of the gambling industry, and constituting a structural influence that normalises the activity among young people. Through a qualitative inquiry, this study investigates the social agentic factors of individuals who are susceptible to gambling. Fifteen non-gamblers were recruited across three commercial cities in Africa; Nairobi, Lagos, and Johannesburg. We first established the gambling susceptibility of the participants; their need for money, their passion for football, ownership of a smartphone, access to the Internet, and exposure to football gambling marketing. Consequently, we probed for their agency, which is indicative of why they do not gamble, despite being susceptible to engaging in the activity. As such, these factors may be utilised to develop an intervention programme for gamblers within the geographical context.